Pengaruh Variasi Panjang Velocity Stack Terhadap Daya Motor Bensin Satu Silinder 150 CC - Zaidan Almeyda; Ahmad Hanif Firdaus (Pusat Riset dan Inovasi Nasional, 2024)
The automotive industry is growing rapidly, especially on 150 cc motorcycles. Problems related to lack of engine performance are the main focus in making modifications. Velocity stack in standard conditions is an air duct that connects the throttle body with the air filter box. The standard velocity stack is made of rubber so that it can be deformed when the vacuum is high and the shape has a curve so that it can inhibit airflow. Manufacturers make velocity stacks with consideration of their short length in order to produce optimal engine performance. The purpose of this study was to determine the effect of variations in stack velocity length on the power of a 150 CC single-cylinder gasoline motor. The independent variable in this study was the variation in velocity stack length of 90 mm (standard), 110 mm, 70 mm, and 50 mm. The variables tied to this study were power, specific fuel consumption, and exhaust emissions. The control variable in this study was fuel with 98 octane. The power test method uses a dyno test tool and a velocity stack with a length of 70 mm produces 15.82 Hp (0.42 Hp higher) than when using a 90 mm velocity stack (standard) of 15.4 Hp at 8000 rpm engine speed.